1982
DOI: 10.1007/bf00745020
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane ferricyanide reduction by cells of the yeastSaccharomyces cerevisiae

Abstract: Both respiratory-competent and respiratory-deficient yeast cells reduce external ferricyanide. The reduction is stimulated by ethanol and inhibited by the alcohol dehydrogenase inhibitor, pyrazole. The reduction of ferricyanide is not inhibited by inhibitors of mitochondrial or microsomal ferricyanide reduction. Cells in exponential-phase growth show a much higher rate of ferricyanide reduction. The reduction of ferricyanide is accompanied by increased release of protons by the yeast cells. We propose that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Crane et al reported a stoichiometric export of electrons and protons during ferricyanide reduction by yeast cells (12). With cultured carrot cells, however, Craig and Crane (11) observed a proton export which was 3-fold the reduction rate offerricyanide.…”
Section: Trans-plasma Membrane Electron Transfermentioning
confidence: 99%
“…Crane et al reported a stoichiometric export of electrons and protons during ferricyanide reduction by yeast cells (12). With cultured carrot cells, however, Craig and Crane (11) observed a proton export which was 3-fold the reduction rate offerricyanide.…”
Section: Trans-plasma Membrane Electron Transfermentioning
confidence: 99%
“…In Escherichia coli, specific ferric binding compounds termed siderophores are secreted that bind and solubilize environmental iron and deliver it to specific receptors for transport across the outer and inner membranes (2). In the yeast Saccharomyces cerevisiae, the major iron uptake system under aerobic conditions depends on a transplasma membrane electron transport system (3,4) that reduces ferric iron external to the cell. Multicellular eukaryotes may also use an externally directed ferric reductase prior to transmembrane movement of ferrous iron (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…An alternative mechanism has been proposed in which environmental ferric iron is initially solubilized by reduction, and the ferrous iron is then transported across the plasma membrane (9,25). A plasma membrane reductase activity able to reduce ferric iron has been observed in some bacterial strains, fungi, and plant and animal cells (3,5,16,19,22,29,30); however, it has not been possible to link the observed reductase activities with iron uptake. The latter is important because ferric reductase can be utilized in the plasma membrane for functions other than iron uptake.…”
mentioning
confidence: 99%
“…These cells have an externally directed ferric reductase activity in the plasma membrane that is regulated by the concentration of iron in the growth medium (5,15). We isolated a mutant lacking this plasma membrane reductase activity.…”
mentioning
confidence: 99%